Heavy metal enrichment in the intermediate He-sdOB pulsator Feige 46 - Latour, Marilyn; Dorsch, Matti; Heber, Ulrich (Astronomy & Astrophysics, 2019)
The intermediate He-enriched hot subdwarf star Feige 46 was recently reported as the second member of the V366 Aqr (or He-sdOBV) pulsating class. Feige 46 is very similar to the prototype of the class, LS IV-14 degrees 116, not only in terms of pulsational properties, but also in terms of atmospheric parameters and kinematic properties. LS IV-14 degrees 116 is additionally characterized by a very peculiar chemical composition, with extreme overabundances of the trans-iron elements Ge, Sr, Y, and Zr. We investigate the possibility that the similarity between the two pulsators extends to their chemical composition. We retrieved archived optical and UV spectroscopic observations of Feige 46 and performed an abundance analysis using model atmospheres and synthetic spectra computed with TLUSTY and SYNSPEC. In total, we derived abundances for 16 elements and provide upper limits for four additional elements. Using absorption lines in the optical spectrum of the star we measure an enrichment of more than 10 000x solar for yttrium and zirconium. The UV spectrum revealed that strontium is equally enriched. Our results confirm that Feige 46 is not only a member of the now growing group of heavy metal subdwarfs, but also has an abundance pattern that is remarkably similar to that of LS IV-14 degrees 116.
Keywords: stars: abundances; subdwarfs; stars: individual: Feige 46